AYURVEDIC MEDICINE PREPARATIONS WITHIN THE MANAGEMENT OF WHITE DISCHARGE - Dr. Usha Jangir (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2017)
Leucorrhoea is a terrible symptom within the lifetime of girls and is extremely usually ascertained symptom in currently day’s gynecological practices. Once the discharge is pathological it causes associated complains like fanny cutaneous sensation, low aching, frequent wetting of under garments and restlessness. Thanks to the agitated schedule of girl in epoch there's lack of your time to keep up physical and psychological state standing. The trendy era, competitive milestones, fast food, late night meals, consumption of alcohol and inadequate sleep resulted within the trying conditions distrurbing the secretion balance inflicting discharge abnormalities ie. asrigdara, atyaartava,vandhya yoni etc. Keywords- Leucorrhoea, asrigdara, yoni vyapada, vandhya.